Biogeochemistry and microbiology of high Arctic marine sediment ecosystems—Case study of Svalbard fjords. Issue Volume 66:Issue S1(2021) Supplement (10th August 2020) - Jørgensen, Bo Barker; Laufer, Katja; Michaud, Alexander B.; Wehrmann, Laura M.
Abstract: Fjord ecosystems of the high Arctic are distinct from fjords of temperate latitudes due to the influence of glaciers, icebergs, sea ice, and the permanently low temperatures. The sediment microbiology and biogeochemical processes were analyzed during an international research program with multiple field studies in Svalbard, situated between the Barents Sea and the Arctic Ocean. We here describe the physical and geochemical setting and the predominant microbiological processes in several fjords. Physiological studies of sediments and pure cultures show how the predominantly psychrophilic bacteria are adapted to the near‐zero temperature. The microbial communities include bacteria responsible for organic matter hydrolytic degradation, fermentation, and terminal oxidation to CO2 . These processes drive the cycling of carbon, sulfur, iron, and manganese. The balance between the dominant sediment microbial processes changes along transects out through the fjords, reflecting the varying impact of the glacier‐derived rock flour, rich in metal oxides at the head, and the plankton‐derived, labile, marine organic matter at the mouth. Due to accelerated warming of Arctic ecosystems, glaciers are retreating with impacts on the physical, chemical, and biological functioning of the fjord sediment ecosystems.